(untitled) (Journal of Informatics and Mathematical Sciences, 2012)
This paper deals with the unique extension of a finite regular set function from the δ-lattice of all compact G_δ-subsets of a locally compact Hausdorff space to a finite regular measure on the δ-ring of all relatively compact Borel subsets of the space. This extension is a two-step method because it is performed (without density assumptions) via the δ-ring of all relatively compact Baire subsets of the space.